TINJAUAN PENGGUNAAN ANTIBIOTIKA PADA PASIEN SEKSIO SESAREA DI BLU RSUP. PROF. DR. R. D. KANDOU MANADO PERIODE JANUARI – DESEMBER 2011 - Tanan, Desye Nurmalita; Tjitrosantoso, Heedy M; Fatimawali, Fatimawali (PHARMACON, 2012)
This research aims to describe the antibiotics use in caesarean section patients due to its kind,route of administration, conformity of dose and frequency, and length of time given. It is adescriptive research. The data were collected in retrospective on 129 patients medical recordswhose received antibiotics, both prophylactic antibiotics and therapeutical antibiotics. Dataobtained shows that the third generation of cephalosporin which is ceftriaxone combined withmetronidazole (55.81%) is the most common kind of antibiotic that being used asprophylactic antibiotics and the most common therapeutical antibiotic that being used is thefirst generation of cephalosporin which is cefadroxil combined with metronidazole (53,59%).The prophylactic antibiotic’s route of administration is intravenously (IV) (100%) and oralfor therapeutical antibiotics (100%). The antibiotics doses that are being used bothprophylactic antibiotics and therapeutical antibiotics has been fulfilled the conformity of doseand frequency, with the longest duration of usage the prophylactic antibiotics is 1 day(80,92%).Keywords: antibiotics, surgical wound infections, caesarean section